Transcriptome analysis of Stagonospora nodorum: gene models, effectors, metabolism and pantothenate dispensability - Ipcho, S.; Hane, J.; Antoni, E.; Ahren, D.; Henrissat, B.; Friesen, T.; Solomon, P.; Oliver, Richard (Wiley-Blackwell Publishing Ltd., 2011)
The wheat pathogen Stagonospora nodorum, causal organism of the wheat disease Stagonospora nodorum blotch, has emerged as a model for the Dothideomycetes, a large fungal taxon that includes many important plant pathogens. The initial annotation of the genome assembly included 16 586 nuclear gene models. These gene models were used to design a microarray that has been interrogated with labelled transcripts from six cDNA samples: four from infected wheat plants at time points spanning early infection to sporulation, and two time points taken from growth in artificial media. Positive signals of expression were obtained for 12 281 genes. This represents strong corroborative evidence of the validity of these gene models. Significantly differential expression between the various time points was observed. When infected samples were compared with axenic cultures, 2882 genes were expressed at a higher level in planta and 3630 were expressed more highly in vitro. Similar numbers were differentially expressed between different developmental stages. The earliest time points in planta were particularly enriched in differentially expressed genes. A disproportionate number of the early expressed gene products were predicted to be secreted, but otherwise had no obvious sequence homology to functionally characterized genes. These genes are candidate necrotrophic effectors.We have focused attention on genes for carbohydrate metabolism and the specific biosynthetic pathways active during growth in planta. The analysis points to a very dynamic adjustment of metabolism during infection. Functional analysis of a gene in the coenzyme A biosynthetic pathway showed that the enzyme was dispensable for growth, indicating that a precursor is supplied by the plant.